Influence of maturation and gender on performance at the 2009 MTB World Championships: Terrain specific comparisons - Higham, D.; Abbiss, C. R.; Ross, M. L. R.; Garvican, L.; Ross, N.; Wraith, E.; Dingley, A.; Martin, D. T. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
For Cross-country cycling (aka Mountain Bike; MTB), three age groups categories are recognised at the UCI World Championships: 1) Juniors (Jr: <19 years), 2) Under 23 years (U23) and 3) Elite. At the 2009 MTB World Championships in Canberra, eighteen countries entered teams into the team relay event which requires three men (one representative male from each of the different age categories) and one elite woman to complete one lap each of the World Championship Cross-country course. This unique event makes it possible to evaluate the influence of maturation from Jr to elite on Cross-country performance and also allows for a comparison between elite men and elite women. More specifically, by dividing up the Cross-country course into sections based on specific types of terrain, it becomes possible to identify the types of terrain where women and Jr / U23 men lose the most time compared with the elite men. While several studies have characterised the physiological profile of successful mountain bikers, we are unaware of research that has specifically documented the influence of maturation and gender using the most successful MTB cyclists in the world. The purpose of this study was to compare lap times and terrain specific splits across male MTB cyclists competing in different age categories as well as to compare elite male and female competitors using competition data collected during the relay event. We were specifically interested in establishing sections during the race Jr / U23 men and Elite women lost time compared with the elite men. Methods Data were collected on the top 10 competitors for each male age category (Jr, U23, Elite) and the elite women racing in the team relay event at the 2009 UCI Cross-country Mountain Bike World Championships (Canberra, Australia). This event required each of the four members of the relay team to race one lap of the hilly 6.47 km circuit (25.88 km in total). Split performance times were quantified using a video analysis system recording at a frequency of 25 Hz, which was synchronized with the official timing system (Omega, Swatch Group, Swiss). The video analysis system included eight digital cameras located at various positions on the course defining sections of technical (T) and non-technical (NT), climbing, decending and rolling/flat cycling. Distinctions between these sections were determined by two national cross-country MTB coaches. Data from the top 10 finishers for each of the four categories of racing were documented to establish how much slower Jr males, U23 males and Elite females were compared with Elite males. In addition, terrain specific evaluations were made to establish where on the course Elite male gained time. Results Average overall lap times for the fastest 10 competitors in each maturation and gender category were: Elite Men (17:45, min:sec), U23 Men (18:05), Jr Men (18:28) and Elite Women (20:51). Thus, compared to Elite Men, U23 Men were 1.8% slower, Jr Men were 4.0% slower and Elite Women were 17.4% slower. Although lap times for the Elite Women were the slowest, the distribution of time spent in each of the different terrain categories was distributed similarly to results produced by elite men (M vs. F; Split1 17% v 17%; Split2 19% v 20%; Split3 7% v 8%; Split4 12% v 11%; Split5 10% v 10%; Split6 5% v 5%; Split7 9% v 8%; Split8 21% v 20%). As expected, Elite Women lost the largest portion of time when compared with Elite Men over nontechnical (~40 s) and technical climbing (~40 s). Junior Men lost ~10 s to Elite Men over Splits 1, 5, and 8 but Under23 Men only lost ~5 s to Elite Men over Spits 1 and 2 and ~2 s over Splits 7 and 8, essentially matching Elite Men through technical flat sections of the course. An overall correlation between the times identified for all competitors (n=18 teams x 4 athletes) on each split (n=8) to the overall lap time highlighted that the sections of the course most predictive of overall lap time were Splits 1 and 2 (r=.93) which were non-technical and technical climbing (also longest splits on the course). Discussion/Conclusion Over a 6.47 km MTB circuit, Elite Male competitors establish the fastest times followed by U23 Men (-1.8%), Jr Men (-4.0%) and Elite Women (-17.4%). For Elite Women, there was no single section of terrain that was primarily responsible for the slower times as time was lost when compared to Elite Men over all types of terrain. U23 Men and Jr Men tended to match Elite Men over technical flat sections and technical descents but were noticeably slower during technical and non-technical climbing. U23 Men made time on Jr Men during the nontechnical climbing sections. A key aspect of maturation in male MTB cyclists is the ability to maintain competitive speeds up prolonged non-technical climbing. Interestingly, world championship level Jr Male MTB cyclists are able to match the elite men over many technical sections of the course.